Nightingale Garden near the Sea: on the Question of Akhmatov’s Intertext in A. Blok’s poem Nightingale Garden - Pakhareva, Tatiana (Literatūra, 2023)
The article aims to clarify and supplement the picture of the poetic dialogue between Anna Akhmatova and A. Blok in winter 1913–1914. The period of intense communication between the poets and their mutual dedications exchange (“Beauty is terrible” – you will be told ... by Blok and I came to the poet visit ... by Akhmatova) is also the time when Blok began work on Nightingale Garden. The article reveals numerous overlaps with the lyrics of Evening and Rosary mainly in draft versions of Blok’s poem, as well as some parallels with Akhmatova’s poem Near the Sea, created simultaneously with Nightingale Garden and published six months before the end of Blok’s work on his poem. The sources of the identified overlaps are mainly those poems of Akhmatova that are marked by Blok’s marginalities on a copy of the Rosary, which he received from Akhmatova in spring 1914. Everything above mentioned suggests that the whole Akhmatova’s intertextual field that appeared in the early versions of the Nightingale Garden is nonrandom. However, the majority of the figurative and intonational-syntactic coincidences with the Akhmatova’s poems were not included in the final text of the Nightingale Garden, so as a result, the process of Blok’s work on the poem clearly captures both the dynamics and internal logic of his exit from a fledgling, but active poetic dialogue with Akhmatova, and a significantly greater degree of the Blok’s initial involvement in this dialogue than has been assumed until now.
Keywords: Akhmatova; Blok; “Nightingale Garden”; poetic dialogue; intertextuality; motif